Magnetic nanocrystallites strontium hexaferrite as an efficient catalyst in the green Betti reaction. Issue 10 (3rd October 2018) - Mohammadi Ziarani, Ghodsi; Kazemi Asl, Zhila; Gholamzadeh, Parisa; Badiei, Alireza; Afshar, Morteza
Abstract: The sol–gel auto-combustion method was applied for preparation of SrFe12 O19 magnetic nanoparticles (MNPs). Then, the prepared SrFe12 O19 was analyzed by VSM, FT-IR, SEM, N2 adsorption-desorption and XRD pattern. According to the hysteresis loops of SrFe12 O19 MNPs, its magnetic saturation was about 79 emu/g and also it is a typical feature of ferromagnetic compound. SEM image showed semi-spherical particles with average size of 70 nm. The BET surface area of SrFe12 O19 MNPs was 10.4 m 2 /g. Moreover, the catalytic activity of SrFe12 O19 MNPs was tested for the first time toward the Betti reaction. The results showed that it is an efficient catalyst which can be easily separated from the reaction mixture using an external magnet and gives the pure products in high yields within short reaction time.